2014
DOI: 10.1073/pnas.1317242111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin 2 along with microRNA-199a reciprocally regulate hypoxia-inducible factors and ovarian cancer metastasis

Abstract: Hypoxia-driven changes in the tumor microenvironment facilitate cancer metastasis. In the present study, we investigated the regulatory cross talk between endocytic pathway, hypoxia, and tumor metastasis. Dynamin 2 (DNM2), a GTPase, is a critical mediator of endocytosis. Hypoxia decreased the levels of DNM2. DNM2 promoter has multiple hypoxia-inducible factor (HIF)-binding sites and genetic deletion of them relieved hypoxia-induced transcriptional suppression. Interestingly, DNM2 reciprocally regulated HIF. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…Several studies have described miR-199a as a type of miRNA associated with hypoxia-adaptation (36)(37)(38)(39). It was demonstrated that miR-199a-5p downregulation is AKT-dependent (39,40) and may be antagonized by the β-adrenergic receptor (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described miR-199a as a type of miRNA associated with hypoxia-adaptation (36)(37)(38)(39). It was demonstrated that miR-199a-5p downregulation is AKT-dependent (39,40) and may be antagonized by the β-adrenergic receptor (40).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, miR-199 inhibits growth and peritoneal seeding of ovarian tumors after i.p. injection of SKOV3 and A2780 cells (70,71). In these models total tumor burden and number of metastases on the peritoneal surface, omentum, small bowel mesentery and both ovaries were reduced.…”
Section: Mir-138mentioning
confidence: 96%
“…miR-199 is down-regulated in the majority of EOCs and has been shown to directly target pro-metastatic proteins such as c-MET, HIF-1α, HIF-2β and Iĸ kinase β IKKβ in this tumor entity (Figure 3) (70-72). In EOC cell lines, miR199 inhibits proliferation, invasion and adhesion as well as extracellular signal regulated kinase and nuclear factor ĸB (NFĸB) signaling (70)(71)(72). Inhibition of HIF levels, down-regulates lysyl-oxidase (LOX), a matrix remodeling enzyme which cross-links collagens (73).…”
Section: Mir-138mentioning
confidence: 99%
“…High ALDH1 expression was associated with chemoresistance in in vitro and ex vivo samples [26]. Besides, miR-200 family [27][28][29][30], miR-199/214 cluster [31][32][33][34][35], miR-31 [36] et al, are also reported to be connected with chemotherapy resistance, including cisplatin and pactitaxel (Table 1). [25] miR-591 ZEB1 Paclitaxel resistance [25] miR-23b ALDH1 Chemoresistance [26] miR-27a ALDH1 Chemoresistance [26] miR-27b ALDH1 Chemoresistance [26] miR-346 ALDH1 Chemoresistance [26] miR-424 ALDH1 Chemoresistance [26] miR-503 ALDH1 Chemoresistance [26] miR-200 family…”
Section: Micrornasmentioning
confidence: 96%
“…IKKβ, HIF-1A, HIF-2A CD44 JAG1 PTEN, CCL5 Chemosensitivity Chemosensitivity Cisplatin sensitivity Cisplatin resistance [32,33] [31]…”
Section: Micrornasmentioning
confidence: 99%